Effects of Ethanolic Cinnamon (Cinnamomum cassia) Extract on Performance of Broiler Chickens. - Odutayo, O.J.; Adewole, F.A.; Adeyemo, A.A.; Ibigbami, D.J.; Iyanda, A.I.; Sogunle, O.M. (Nigerian Journal of Animal Science, 2026)
A total of 200-day-old chicks were used to investigate the effect of ethanolic cinnamon extract (ECE) on the performance of broiler chickens. The chicks were brooded collectively for two weeks and thereafter balanced for weight and assigned to six treatments replicated four times (10 birds/replicate) in a completely randomized design. Treatments consist of positive control (broad spectrum antibiotics); negative control (no antibiotics/cinnamon extracts); 20, 40 and 60ml millilitres of ethanolic extract into 1 liter of drinking water, respectively. Data collected on the response variables were subjected to One-way Analysis of Variance. Result revealed that birds on 20 to 60 ml ECE had improved MCHC which ranges between 33.50 to 33.55 g/dl; heterophils was increased in birds under 20ml (42.00 %) and 60ml (41.50 %) ECE. Serum total proteins were significantly elevated due to administration of 20 ml (8.50 g/dl) and 60ml (9.00 g/dl) ECE relative to other treatments; globulin value was enhanced due to 60ml (4.50g/dl) ECE. In conclusion, for improved productive performance indices (haematobiochemical indices) in broiler chickens the utilization of ethanolic cinnamon extract at the rate of 60ml thrice a week is appropriate.